Cleavage furrow formation and ingression during animal cytokinesis - D'Avino, Pier Paolo (Henry Stewart Talks, 2009)
Co-ordination of multiple events during cytokinesis, Assembly and contraction of the actomyosin ring: the role of RhoA, Cleavage plane determination, The role of microtubules in positioning the cleavage plane, The molecular nature of the furrow inducing signal, The centralspindlin complex, The role of Anillin during cytokinesis, Interaction between Anillin and centralspindlin connects the contractile ring with spindle microtubules, Membrane formation during cytokinesis, The origin of new membrane for the cleavage site, Molecules involved in membrane trafficking during cytokinesis, The multiple roles of the RacGAP component of the centralspindlin complex during cytokinesis